The effect of dietary fish oil on weight gain and insulin sensitivity is dependent on APOE genotype in humanized targeted replacement mice. Issue 3 (28th November 2016) - Slim, Kenna E.; Vauzour, David; Tejera, Noemi; Voshol, Peter J.; Cassidy, Aedin; Minihane, Anne Marie
ABSTRACT: We investigated the independent and interactive impact of the common APOE genotype and marine n‐3 polyunsaturated fatty acids (PUFAs) on the development of obesity and associated cardiometabolic dysfunction in a murine model. Human APOE3 and APOE4 targeted replacement mice were fed either a control high‐fat diet (HFD) or an HFD supplemented with 3% n‐3 PUFAs from fish oil (HFD + FO) for 8 wk. We established the impact of intervention on food intake, body weight, and visceral adipose tissue (VAT) mass; plasma, lipids (cholesterol and triglycerides), liver enzymes, and adipokines; glucose and insulin during an intraperitoneal glucose tolerance test; and Glut4 and ApoE expression in VAT. HFD feeding induced more weight gain and higher plasma lipids in APOE3 compared to APOE4 mice ( P < 0.05), along with a 2‐fold higher insulin and impaired glucose tolerance. Supplementing APOE3, but not APOE4, animals with dietary n‐3 PUFAs decreased body‐weight gain, plasma lipids, and insulin ( P < 0.05) and improved glucose tolerance, which was associated with increased VAT Glut4 mRNA levels ( P < 0.05). Our findings demonstrate that an APOE3 genotype predisposes mice to develop obesity and its metabolic complications, which was attenuated by n‐3 PUFA supplementation.—Slim, K. E., Vauzour, D., Tejera, N., Voshol, P. J., Cassidy, A., Minihane, A. M. The effect of dietary fish oil on weight gain and insulin sensitivity is dependent on APOE genotype in humanized targeted replacement mice. FASEB J. 31, 989–997 (2017). www.fasebj.org